2021
DOI: 10.1097/md.0000000000027412
|View full text |Cite
|
Sign up to set email alerts
|

The irony of the transforaminal approach

Abstract: Transforaminal endoscopic lumbar discectomy (TELD) is useful for soft lumbar disc herniation (LDH). Although the transforaminal approach can reach the foraminal disc zone, the risk of exiting nerve root irritation along the path is considerable. Few studies have assessed the difficulties of TELD for foraminal LDH. The objective of this study is to compare the clinical results of TELD between foraminal or far-lateral LDH and paramedian LDH. Between June 2016 and July 2017, 135 consecutive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Upper and Lower Lumbar Spine With Each Zone of Disc Herniation A total of 10 articles [31][32][33][34][35][36][37][38][39][40] advocated for the TELD approach at higher and lower lumbar levels with each zone (central, subarticular, foraminal, or extraforaminal zone) of the herniated disc. Only 1 study, conducted by Li and Zhou, 37 reported that TELD could be performed in all zones and at all lumbar levels of herniated discs.…”
Section: Transforaminal Endoscopic Lumbar Discectomy Approachmentioning
confidence: 99%
“…Upper and Lower Lumbar Spine With Each Zone of Disc Herniation A total of 10 articles [31][32][33][34][35][36][37][38][39][40] advocated for the TELD approach at higher and lower lumbar levels with each zone (central, subarticular, foraminal, or extraforaminal zone) of the herniated disc. Only 1 study, conducted by Li and Zhou, 37 reported that TELD could be performed in all zones and at all lumbar levels of herniated discs.…”
Section: Transforaminal Endoscopic Lumbar Discectomy Approachmentioning
confidence: 99%